Procedure: History, Current State and Perspectives - D. Valeev; N. Makolkin (BRICS Law Journal)
This article is devoted to the results of the VI annual Symposium of the journal “Herald of Civil Procedure” held on 27 and 28 September 2019 on the premises of the Faculty of Law of the Kazan (Volga Region) Federal University (KFU). The Symposium took place with the participation of the editorial board of the journal “Civil Law Review” and was titled “2019 – Civil Law and Procedure: History, Current State and Perspectives (Coinciding with the Bicentennial of D.I. Meyer).” The editorial board of the journal “Herald of Civil Procedure” annually invites outstanding legal scholars and practitioners in the field of civil procedure to Kazan to attend the Symposium of the journal “Herald of Civil Procedure”. In only six years, the Symposium has become not only an annual tradition, but also a brand name. The Symposium is an anchor event not only of the Law Faculty of the KFU, but also of the entire Kazan Federal University, which each year cordially welcomes leading civil procedure scholars. In addition, the Symposium hosts participants, friends and interested listeners, and has created a platform for large-scale discussions at the highest level The first and each subsequent Symposium are consistent in scope and organization. Yet, each year something new appears, some highlight that gives the event a unique character and momentum for moving forward, developing, improving and raising the level of engagement.